Pengaruh Jurnalisme Warga Terhadap Peningkatan Partisipasi Masyarakat Mengakses Instagram Akun Makassar Info - Jundullah Muh. Ali Gufron; Indah Pratiwi Manggaga (IQTIDA : Journal of Da'wah and Communication, 2022)
Citizen journalism continues to grow with supports such as smartphones or laptops that can be used to record and send images easily, hence, that the general public can be involved in the process of disseminating information and news. The purpose of this study was to determine the effect of citizen journalism on increasing access to Makassar Info's Instagram account and to determine the level of public participation in accessing Makassar Info's Instagram. This study used a quantitative descriptive method. The data collection technique in this study used primary data, which is data obtained directly from the results of the questionnaire (questionnaire). The results of this study indicate that citizen journalism has a positive and significant effect on increasing public participation in accessing Instagram Makassar Info. The level of community participation in providing information to Makassar Info Instagram is still in the very low category, this is evidenced by 100 respondents, there are 42 (42.0%) respondents who say that they rarely send information to Makassar Info Instagram, but judging by the public participation in accessing Makassar Info Instagram, including in the high category, this is evidenced from 100 respondents there are 40 (40.0%) often and (18.0%) respondents who say very often access Makassar Info Instagram. From the research findings, it can be concluded that the Makassar Info Instagram admin generally responds to the contents of their followers' messages within 10 to 20 minutes, besides that the majority of messages sent by followers are in the form of photos or videos